2021
DOI: 10.1021/acsaem.1c02382
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lithium Storage Property Boosted by Hierarchical Hollow-Structure WSe2 Nanosheets/N, P-Codoped Carbon Nanocomposites

Abstract: Developing hierarchical nanostructures composed of transition-metal dichalcogenides and hollow carbon matrixes is one of the attractive avenues in energy storage and conversion field on account of their unique the synergistic effect and stable architecture. Herein, N, P-codoped hollow carbon nanocomposites combined with WSe2 nanosheets were fabricated via a robust strategy including a metal chelation coordination method and high-temperature selenization treatment. Such a typical hollow structure can offer nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Another example, WSe 2 /NPCs nanocomposite, was given by Wang et al. [ 287 ] WSe 2 , as one of the TMDCs, has attracted tremendous attention on account of the attractive energy density, higher reversible capacity, and faster ion diffusion rate owing to the larger interlamellar space (≈6.50 Å). However, the severe aggregation and poor conductivity of WSe 2 lead to the inferior cycling ability and attenuation of capability.…”
Section: Application Of 2d Materials For Monovalent Mhcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example, WSe 2 /NPCs nanocomposite, was given by Wang et al. [ 287 ] WSe 2 , as one of the TMDCs, has attracted tremendous attention on account of the attractive energy density, higher reversible capacity, and faster ion diffusion rate owing to the larger interlamellar space (≈6.50 Å). However, the severe aggregation and poor conductivity of WSe 2 lead to the inferior cycling ability and attenuation of capability.…”
Section: Application Of 2d Materials For Monovalent Mhcsmentioning
confidence: 99%
“…Since then, different kinds of TMDCs have emerged and been fully used in LIHCs, including CoS, [282] MoSe 2 , [283] MoS 2 , [284][285][286] and WSe 2 . [287] In 2019, based on simple and efficient hydrothermal method, a CoS nanosheets self-assembled 3D hierarchically structure (Figure 17d,e) was synthesized by Kong's group. [282] The obvious charge-discharge plateau in GCD curves suggested a conversion-type storage mechanism and a specific capacity of 434 mAh g −1 can be observed (Figure 17f).…”
Section: D Tmdcsmentioning
confidence: 99%
“…Furthermore, the 3DRG electrode shows a much bigger specific capacity than the theoretical capacity of ReS 2 (∼430 mAh g −1 ) in Figure 5d, which was previously reported in many research studies on TMD-based composite anodes. 10,47,48 A reasonable explanation can be summarized as follows. In general, nanostructured electrode materials have stronger lithium storage capabilities than the corresponding bulk or large-size electrode materials.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…[ 18,19 ] Moreover, our group developed a series of M‐PDA composites for electrochemical performance such as W‐PDA and Mo‐PDA composites. [ 20–22 ] It was found that the content of reactants and the ratio of solvents always play an important role in the final morphology. For bimetallic dopamine composites, multicomponent design and structural modulation can effectively improve electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Moreover, our group developed a series of M-PDA composites for electrochemical performance such as W-PDA and Mo-PDA composites. [20][21][22] It was found that the content of reactants and Metal-polydopamine coordination chemistry attracts great attention owing to the synergistic effect of adjustable components and advantageous structures. However, few efforts have been devoted to exploring bimetal-polydopamine composites, especially for multistructural composites with high-capacity components and high stability.…”
mentioning
confidence: 99%